Magnetic composite material and preparation method thereof
By adding specific deodorant composition to the magnetic composite, the problem of irritating odors generated during use of magnetic composite materials is solved, and the odor elimination and application safety of the material are improved.
Patent Information
- Application Number
- CN202311390088.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
Existing magnetic composites will produce irritating odors during use, such as ammonia, which will affect the application of the product and the safety of the operator.
A magnetic composite material preparation method is adopted, which includes 75 to 90 parts by mass of magnetic powder, 10 to 25 parts by mass of binder and 0.3 to 0.8 parts by mass of deodorant. The composition of the deodorant includes calcium chloride, nanosilica, shell powder and diatomaceous earth. It is made by high-speed mixed ball milling and can adsorb or absorb contaminants generated by magnetic powder and binder during the extrusion and granulation process to eliminate the odor of the material.
It effectively eliminates the odor in magnetic composite materials, especially the odor generated by ammonia, improves the application safety and fluidity of the materials, and is suitable for household appliances, automobiles, communication equipment and other fields.
Smart Images

Figure BDA0004512071980000091 
Figure BDA0004512071980000141 
Figure BDA0004512071980000151
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials, relates to injection-molded magnetic materials, and in particular to a preparation method of a magnetic composite material and the composite material. Background Art
[0002] Injection molded magnets are an important branch of bonded magnets. They have the advantages of high dimensional accuracy, good mechanical properties, and the ability to prepare magnets with complex shapes and multi-polar orientations. They are widely used in household appliances, automobiles, communication equipment, testing instruments, computers, office equipment and other fields.
[0003] The preparation requirements of injection molding magnetic materials are relatively high. The injection molding temperature requirements should be met during the injection molding process, and high fluidity is also required to ensure that the granular material can fully fill the mold during the injection molding process. A method for preparing a samarium iron nitrogen magnet disclosed in CN114220648A includes: mixing samarium iron alloy powder with zinc powder and performing a first heat treatment in an ammonia atmosphere, followed by a second heat treatment in a nitrogen atmosphere to obtain samarium iron nitrogen magnetic powder; mixing the samarium iron nitrogen magnetic powder with an adhesive and pressing to obtain a samarium iron nitrogen magnet. It uses nitrogen and ammonia to infiltrate nitrogen into the samarium iron alloy, but due to process and other conditions, the nitrogen element cannot be completely infiltrated, so that part of the ammonia that has not been infiltrated is adsorbed on the surface of the magnetic powder, which will evaporate with the magnetic powder product in the later stage, so that the product will volatilize an unpleasant ammonia smell for a long time, seriously affecting the application of the product.
[0004] CN106349686A discloses a high-performance polyamide / samarium iron nitrogen magnetic composite material and its preparation method. In the first step, polyphenylene sulfide resin is used as a matrix, and toughening agent, lubricant and antioxidant are used together with a twin-screw extruder to prepare a multifunctional masterbatch; in the second step, the surface-treated samarium iron nitrogen powder and the masterbatch prepared in the first step are used together with a twin-screw extruder to prepare a magnetic composite material, which has high fluidity, magnetic properties and good mechanical properties, and is suitable for manufacturing devices by injection molding. CN111403165A discloses a samarium iron nitrogen / nano iron composite bonded permanent magnet preparation method, which includes the following steps: (1) using a chemical vapor deposition method to coat a layer of nano-Fe film on the surface of the samarium iron nitrogen powder; (2) performing an anti-oxidation coating treatment on the surface of the samarium iron nitrogen / nano iron powder; (3) mixing and granulating; (4) preparing the composite bonded magnet by injection molding or calendering, molding, and extrusion. Due to the soft and hard magnetic nano dual-phase coupling effect, the magnetic properties of anisotropic and isotropic SmFeN bonded magnets are significantly improved.
[0005] However, some small molecules in the polyamide used in the above preparation method have poor temperature resistance, which will cause high-temperature degradation of the material. In addition to producing gases such as N2 and CO, a small amount of ammonia and formamide will also be produced, which have a pungent odor and will slowly be released from the product, posing a threat to the safety of operators. Ultimately, the smell of the composite magnetic material product will be further aggravated in the later stage, affecting the application of the product.
[0006] The existing technologies are mainly aimed at improving the magnetic properties and fluidity of materials, but ignore the impact of odor volatilization on the application in actual product applications. Therefore, how to eliminate the odor of magnetic composite materials has become an urgent problem to be solved. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a magnetic composite material and a preparation method thereof, which can reduce the odor of the magnetic composite material and eliminate the influence of the odor on product application.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a magnetic composite material, which comprises, by weight:
[0010] Magnetic powder 75-90 parts by mass;
[0011] 10 to 25 parts by weight of binder;
[0012] Deodorant 0.3-0.8 parts by mass
[0013] The content of the magnetic powder is 75 to 90 parts by mass, for example, it can be 75 parts by mass, 76 parts by mass, 78 parts by mass, 80 parts by mass, 82 parts by mass, 83 parts by mass, 85 parts by mass, 86 parts by mass, 87 parts by mass, 88 parts by mass, 89 parts by mass or 90 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0014] The content of the binder is 10 to 25 parts by mass, for example, it can be 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, 15 parts by mass, 16 parts by mass, 18 parts by mass, 20 parts by mass, 21 parts by mass, 22 parts by mass, 23 parts by mass, 23 parts by mass or 25 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0015] The content of the deodorant is 0.3 to 0.8 parts by mass, for example, it can be 0.3 parts by mass, 0.35 parts by mass, 0.4 parts by mass, 0.45 parts by mass, 0.5 parts by mass, 0.55 parts by mass, 0.6 parts by mass, 0.65 parts by mass, 0.7 parts by mass, 0.75 parts by mass or 0.8 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] The magnetic composite material of the present invention is compounded by a binder and magnetic powder, which is beneficial to improving the magnetic properties of the material; the added deodorant can adsorb or absorb pollutants generated by the magnetic powder and the binder during the extrusion granulation process, and eliminate the odor of the material, especially the odor generated by ammonia.
[0017] The magnetic composite material provided by the present invention has strong applicability and can be widely used in the fields of household appliances, automobiles, communication equipment, testing instruments, computers, office equipment, etc.
[0018] As a preferred technical solution of the present invention, the magnetic powder includes at least one of samarium iron nitrogen, neodymium iron boron, ferrite, neodymium iron nitrogen and manganese bismuth.
[0019] Preferably, the binder comprises at least one of polyamide, polyolefin and polyester.
[0020] Preferably, the magnetic powder is samarium iron nitride.
[0021] It should be noted that the Curie temperature of SmFeN reaches 476°C, which is significantly higher than that of conventional sintered NdFeB magnets. The anisotropy field is three times that of conventional NdFe-based magnets, and there is no need to add cobalt and / or other heavy rare earth elements to adjust the magnetic properties. It has excellent corrosion resistance and oxidation resistance. Since SmFeN is easily demagnetized during high-temperature use, polyamide with a lower melting point can be selected as the main binder for the preparation of magnetic materials.
[0022] As a preferred technical solution of the present invention, the components of the deodorant include calcium chloride, nano silicon dioxide, shell powder and diatomaceous earth.
[0023] The calcium chloride of the deodorant described in the present invention has a strong adsorption capacity and a low desorption temperature, and can adsorb ammonia in the magnetic composite material to achieve the purpose of rapid deodorization. Nano-silicon dioxide has a porous microstructure and a large specific surface area. It adsorbs and removes ammonia through the process of physical adsorption and chemical decomposition, increases the deodorization area, and can also play a long-term bactericidal and antibacterial role. Shell powder is a porous fiber structure with good adsorption and antibacterial properties, achieving the effect of removing odor. Diatomaceous earth has adsorption performance and high stability, and can effectively remove odor. The present invention adopts a method of high-speed mixing and ball milling of calcium chloride, nano-silicon dioxide, shell powder and diatomaceous earth to prepare the deodorant.
[0024] Preferably, the mass of the deodorant is recorded as 100 parts, and the content of calcium chloride is 35-45 parts by mass, for example, it can be 35 parts by mass, 36 parts by mass, 37 parts by mass, 38 parts by mass, 39 parts by mass, 40 parts by mass, 41 parts by mass, 42 parts by mass, 43 parts by mass, 44 parts by mass or 45 parts by mass, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the content of the nano-silicon dioxide is 25 to 35 parts by mass, for example, it can be 25 parts by mass, 26 parts by mass, 27 parts by mass, 28 parts by mass, 29 parts by mass, 30 parts by mass, 31 parts by mass, 32 parts by mass, 33 parts by mass, 34 parts by mass or 35 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the content of the shell powder is 10 to 20 parts by mass, for example, it can be 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, 15 parts by mass, 16 parts by mass, 17 parts by mass, 18 parts by mass, 19 parts by mass or 20 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0027] Preferably, the content of the diatomaceous earth is 10 to 20 parts by mass, for example, it can be 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, 15 parts by mass, 16 parts by mass, 17 parts by mass, 18 parts by mass, 19 parts by mass or 20 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] As a preferred technical solution of the present invention, the magnetic composite material also includes an antioxidant, activated carbon and an auxiliary agent.
[0029] Preferably, the content of the antioxidant is 0.1 to 0.2 parts by mass, for example, 0.1 parts by mass, 0.11 parts by mass, 0.12 parts by mass, 0.13 parts by mass, 0.14 parts by mass, 0.15 parts by mass, 0.16 parts by mass, 0.17 parts by mass, 0.18 parts by mass, 0.19 parts by mass or 0.2 parts by mass, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0030] Preferably, the antioxidant comprises a hindered phenol antioxidant.
[0031] The hindered phenol antioxidant of the present invention is preferably IRGANOX 1098 (N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine).
[0032] Preferably, the content of activated carbon is 0.5 to 1 part by mass, for example, it can be 0.5 part by mass, 0.55 part by mass, 0.6 part by mass, 0.65 part by mass, 0.7 part by mass, 0.75 part by mass, 0.8 part by mass, 0.85 part by mass, 0.9 part by mass, 0.95 part by mass or 1 part by mass, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0033] The activated carbon in the present invention has a good adsorption effect and can effectively adsorb pollutants and eliminate odors.
[0034] As a preferred technical solution of the present invention, the surface of the magnetic powder is coated with an anti-oxidation layer.
[0035] Preferably, the anti-oxidation layer comprises a phosphating agent.
[0036] Preferably, the content of the phosphating agent is 0.5 to 1 part by mass, for example, 0.5 part by mass, 0.55 part by mass, 0.6 part by mass, 0.65 part by mass, 0.7 part by mass, 0.8 part by mass, 0.9 part by mass, 0.95 part by mass or 1 part by mass, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the phosphating agent comprises a phosphate coupling agent.
[0038] The phosphate coupling agent in the present invention can form an anti-oxidation protective film on the outer surface of the magnetic powder to prevent the magnetic powder from being oxidized during the extrusion granulation process, and is also beneficial to improving the dispersibility of the magnetic powder during the mixing process.
[0039] As a preferred technical solution of the present invention, the auxiliary agent also includes one or a combination of at least two of a lubricant, a stabilizer and a plasticizer.
[0040] The lubricant of the present invention includes but is not limited to one of stearic acid, paraffin oil, polyethylene wax or a combination of at least two thereof. The stabilizer includes but is not limited to one of calcium stearate, zinc stearate, PVC (polyvinyl chloride) composite heat stabilizer or a combination of at least two thereof. The plasticizer includes but is not limited to fatty acid plasticizer and / or phthalate plasticizer. The additive added in the present invention can improve the mechanical properties of the material itself.
[0041] Preferably, the lubricant comprises metal stearate and dioctyl nylonate.
[0042] Preferably, the mass ratio of the metal stearate to dioctyl nylonate is (2-4.5):6, for example, 2:6, 2.2:6, 2.5:6, 2.8:6, 3:6, 3.2:6, 3.5:6, 3.8:6, 4:6, 4.2:6 or 4.5:6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] It should be noted that the present invention does not specifically limit the metal stearate, and any metal stearate known to those skilled in the art may be used. For example, calcium stearate, zinc stearate, magnesium stearate, barium stearate, etc. may be used.
[0044] In a second aspect, the present invention provides a method for preparing the magnetic composite material according to the first aspect, the preparation method comprising:
[0045] The magnetic powder is surface treated so that an anti-oxidation layer is formed on the outer surface of the magnetic powder, and then a binder is added and mixed with a deodorant, and extrusion granulation is performed to obtain the magnetic composite material.
[0046] The present invention forms an anti-oxidation layer on the outer surface of the magnetic powder through surface treatment, which can provide protection for the magnetic powder and prevent the magnetic powder from being oxidized during the extrusion granulation process; the binder is compounded with the magnetic powder, which is beneficial to improving the magnetic properties of the material; the added deodorant can adsorb or absorb pollutants generated by the magnetic powder and the binder during the extrusion granulation process, and eliminate the odor of the material, especially the odor generated by ammonia.
[0047] As a preferred technical solution of the present invention, the surface treatment comprises:
[0048] The phosphating agent is dissolved in an organic solvent to obtain a phosphating solution, the magnetic powder is immersed in the phosphating solution, and a heating treatment is performed to evaporate the organic solvent to form the anti-oxidation layer on the outer surface of the magnetic powder. Preferably, the mass of the phosphating solution is recorded as 100%, and the amount of the phosphating agent added is 0.5-1%, for example, it can be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1%, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0049] Preferably, the organic solvent includes anhydrous ethanol or acetone.
[0050] The amount of the organic solvent added is based on the amount that can completely cover the magnetic powder.
[0051] Preferably, the soaking time is 18 to 30 hours, for example, it can be 18 hours, 20 hours, 21 hours, 22 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the temperature of the heating treatment is 70-90°C, for example, it can be 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, 82°C, 83°C, 85°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, the heating treatment time is 6 to 8 hours, for example, it can be 6 hours, 6.3 hours, 6.5 hours, 7 hours, 7.2 hours, 7.5 hours, 7.8 hours or 8 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] The invention volatilizes the organic solvent of the phosphating solution by heating, thereby forming an anti-oxidation layer on the surface of the magnetic powder.
[0055] As a preferred technical solution of the present invention, the mixing comprises: blending the magnetic powder coated with the anti-oxidation layer, the binder and the deodorant at a temperature of 80 to 120°C.
[0056] The mixing temperature is 80-120°C, for example, it can be 80°C, 82°C, 85°C, 88°C, 90°C, 95°C, 98°C, 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the mixing time is 25 to 45 min, for example, 25 min, 28 min, 30 min, 32 min, 35 min, 40 min, 42 min or 45 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] As a preferred technical solution of the present invention, the temperature of the extrusion granulation is 190-220°C, for example, it can be 190°C, 192°C, 195°C, 196°C, 198°C, 200°C, 205°C, 210°C, 215°C, 218°C or 220°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] Preferably, the extrusion granulation adopts a twin-screw extruder.
[0060] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] The present invention provides a magnetic composite material and a preparation method thereof. The surface of magnetic powder is treated to form an anti-oxidation layer on its outer surface, thereby providing protection for the magnetic powder and preventing the magnetic powder from being oxidized during the extrusion granulation process. The binder is compounded with the magnetic powder to improve the magnetic properties of the material. The added deodorant can adsorb or absorb pollutants generated by the magnetic powder and the binder during the extrusion granulation process, thereby eliminating the odor of the material, especially the odor generated by ammonia. At the same time, the added auxiliary agent can improve the mechanical properties of the material itself. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0064] In a specific embodiment, the present invention provides a magnetic composite material, which comprises, by weight:
[0065] Magnetic powder 75-90 parts by mass;
[0066] 10 to 25 parts by weight of binder;
[0067] Deodorant 0.3-0.8 parts by mass
[0068] In some embodiments, the mass of the deodorant is recorded as 100 parts, and the components of the deodorant and the content of each component are:
[0069]
[0070] In some embodiments, the magnetic composite material further comprises an antioxidant, activated carbon and an auxiliary agent. In terms of weight, the content of the antioxidant is 0.1 to 0.2 weight parts, and the content of the activated carbon is 0.5 to 1 weight parts. The auxiliary agent further comprises one or a combination of at least two of a lubricant, a stabilizer and a plasticizer.
[0071] In some embodiments, the lubricant comprises a metal stearate and dioctyl nylonate, wherein the mass ratio of the metal stearate to dioctyl nylonate is (2-4.5):6.
[0072] In some embodiments, the surface of the magnetic powder is coated with an anti-oxidation layer, and the anti-oxidation layer includes a phosphating agent, and the content of the phosphating agent is 0.5 to 1 parts by mass. The phosphating agent includes a phosphate coupling agent.
[0073] In some embodiments, the magnetic powder includes at least one of samarium iron nitrogen, neodymium iron boron, ferrite, neodymium iron nitrogen and manganese bismuth. The binder includes at least one of polyamide, polyolefin and polyester.
[0074] In some embodiments, the magnetic powder is preferably made of samarium iron nitrogen. The Curie temperature of samarium iron nitrogen reaches 476°C, which is significantly higher than that of conventional sintered neodymium iron boron magnets. The anisotropy field is three times that of traditional neodymium iron-based magnets, and there is no need to add cobalt elements and / or other heavy rare earth elements to regulate the magnetic properties. It has excellent corrosion resistance and oxidation resistance. Since samarium iron nitrogen is easily demagnetized during high-temperature use, polyamide with a lower melting point can be selected as the main binder for the preparation of magnetic materials.
[0075] In another specific embodiment, the present invention provides a method for preparing the magnetic composite material in a specific embodiment, the preparation method comprising:
[0076] The magnetic powder is surface treated so that an anti-oxidation layer is formed on the outer surface of the magnetic powder, and then a binder is added and mixed with a deodorant, and extrusion granulation is performed to obtain the magnetic composite material.
[0077] The surface treatment includes:
[0078] The phosphating agent is dissolved in an organic solvent to obtain a phosphating solution, the magnetic powder is immersed in the phosphating solution, and a heating treatment is performed to evaporate the organic solvent to form the anti-oxidation layer on the outer surface of the magnetic powder, the immersion time is 18 to 30 hours, and the heating treatment temperature is 70 to 90°C.
[0079] In some embodiments, the phosphating solution includes a phosphate coupling agent and an organic solvent, and the amount of the organic solvent added is based on the ability to completely cover the magnetic powder. The mass of the phosphating solution is recorded as 100%, and the amount of the phosphating agent added is 0.5-1%. The organic solvent includes anhydrous ethanol or acetone. The present invention volatilizes the organic solvent of the phosphating solution by heating, and forms an antioxidant layer on the surface of the magnetic powder.
[0080] In some embodiments, the mixing includes: blending the magnetic powder coated with the anti-oxidation layer, the binder and the deodorant at a temperature of 80 to 120° C., and the mixing time is 25 to 45 minutes.
[0081] In some embodiments, the extrusion granulation uses a twin-screw extruder, and the temperature of the extrusion granulation is 190-220°C.
[0082] In the following examples, the component parts are all parts by mass, for example, 0.5 part means 0.5 part by mass.
[0083] Example 1
[0084] The present embodiment provides a polyamide samarium iron nitrogen magnetic composite material and a preparation method thereof, wherein the magnetic composite material is recorded as 100 parts by mass, and includes the following components: 87 parts of samarium iron nitrogen powder, 11 parts of polyamide 12 resin (Wanhua nylon 1020), 0.5 parts of phosphate coupling agent, 1 part of activated carbon powder, 0.3 parts of deodorant, 0.1 parts of antioxidant IRGANOX 1098, and 0.1 parts of lubricant. The deodorant is recorded as 100 parts, and the deodorant is prepared by ball-milling 40 parts of calcium chloride, 30 parts of nano-silicon dioxide, 15 parts of shell powder and 15 parts of diatomaceous earth. The lubricant is prepared by mixing calcium stearate and dioctyl nylon acid in a mass ratio of 4:6.
[0085] The preparation method of the polyamide samarium iron nitrogen magnetic composite material of this embodiment comprises the following steps:
[0086] (1) dissolving a phosphate coupling agent in an alcohol solution to obtain a phosphating solution (the amount of the alcohol solution added is based on the amount of the alcohol solution that can completely immerse the samarium iron nitrogen powder, and the amount of the phosphate coupling agent added is 1% of the mass of the phosphating solution), and immersing the samarium iron nitrogen powder in the phosphating solution for 24 hours;
[0087] (2) placing the samarium iron nitrogen powder soaked in step (1) into a drying oven and drying at 80° C. for 8 h to volatilize the alcohol and form an antioxidant layer on the surface of the samarium iron nitrogen powder;
[0088] (3) The samarium iron nitrogen powder, polyamide 12 resin, activated carbon powder, deodorant, antioxidant and lubricant in step (2) are blended at a high speed at 100° C. for 30 minutes according to the proportion, and then extruded and granulated in a twin-screw extruder at a granulation temperature of 200° C. to obtain a polyamide samarium iron nitrogen magnetic composite material.
[0089] Example 2
[0090] The present embodiment provides a polyamide NdFeB magnetic composite material and a preparation method thereof, wherein the magnetic composite material is recorded as 100 parts by mass, and includes the following components: 78 parts of NdFeB powder, 19 parts of polyamide 12 resin (Wanhua nylon 1020), 0.8 parts of phosphate coupling agent, 0.8 parts of activated carbon powder, 0.8 parts of deodorant, 0.2 parts of antioxidant IRGANOX 1098, and 0.4 parts of lubricant. The deodorant is recorded as 100 parts by mass, and the deodorant is prepared by ball-milling 36 parts of calcium chloride, 34 parts of nano-silicon dioxide, 20 parts of shell powder and 10 parts of diatomaceous earth. The lubricant is prepared by mixing calcium stearate and dioctyl nylon acid in a mass ratio of 2.5:6.
[0091] The preparation method of the polyamide NdFeB magnetic composite material of this embodiment comprises the following steps:
[0092] (1) dissolving a phosphate coupling agent in an alcohol solution to obtain a phosphating solution (the amount of the alcohol solution added is based on the amount of the NdFeB powder that can be completely immersed, and the amount of the phosphate coupling agent added is 0.5% of the mass of the phosphating solution), and immersing the NdFeB powder in the phosphating solution for 18 hours;
[0093] (2) placing the NdFeB powder soaked in step (1) into a drying oven and drying at 90° C. for 6 h to volatilize the alcohol and form an anti-oxidation layer on the surface of the NdFeB powder;
[0094] (3) The NdFeB powder, polyamide 12 resin, activated carbon powder, deodorant, antioxidant and lubricant in step (2) are blended at a high speed at 80° C. for 45 minutes according to the proportion, and then extruded and granulated in a twin-screw extruder at a granulation temperature of 210° C. to obtain a polyamide NdFeB magnetic composite material.
[0095] Example 3
[0096] The present embodiment provides a polyolefin NdFeN magnetic composite material and a preparation method thereof. The magnetic composite material is recorded as 100 parts by mass, and includes the following components: 82 parts of NdFeN powder, 15 parts of polyolefin, 1 part of phosphate coupling agent, 0.6 parts of activated carbon powder, 0.7 parts of deodorant, 0.2 parts of antioxidant IRGANOX 1098, and 0.5 parts of lubricant. The deodorant is recorded as 100 parts by mass, and the deodorant is made by ball-milling 43 parts of calcium chloride, 28 parts of nano-silicon dioxide, 12 parts of shell powder and 17 parts of diatomaceous earth. The lubricant is made by mixing calcium stearate and dioctyl nylon acid in a mass ratio of 3:6.
[0097] The preparation method of the polyolefin NdFeN magnetic composite material of this embodiment comprises the following steps:
[0098] (1) dissolving a phosphate coupling agent in an alcohol solution to obtain a phosphating solution (the amount of the alcohol solution added is based on the amount of the NdFeN powder that can be completely immersed, and the amount of the phosphate coupling agent added is 0.6% of the mass of the phosphating solution), and immersing the NdFeN powder in the phosphating solution for 30 hours;
[0099] (2) placing the NdFeN powder soaked in step (1) into a drying oven and drying at 70° C. for 7 h to volatilize the alcohol and form an anti-oxidation layer on the surface of the NdFeN powder;
[0100] (3) The NdFeN powder, polyolefin, activated carbon powder, deodorant, antioxidant and lubricant in step (2) are blended at a high speed at 120° C. for 25 min according to the proportion, and then extruded and granulated in a twin-screw extruder at a granulation temperature of 220° C. to obtain a polyolefin NdFeN magnetic composite material.
[0101] Example 4
[0102] This embodiment provides a polyamide samarium iron nitrogen magnetic composite material and a preparation method thereof, which is different from Example 1 in that: the deodorant is recorded as 100 parts by mass, and the deodorant is prepared by ball-milling 30 parts of calcium chloride, 20 parts of nano-silicon dioxide, 25 parts of shell powder and 25 parts of diatomaceous earth, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0103] Example 5
[0104] This embodiment provides a polyamide samarium iron nitrogen magnetic composite material and a preparation method thereof. The difference from Example 1 is that the deodorant is recorded as 100 parts by mass, and the deodorant is prepared by ball-milling 50 parts of calcium chloride, 35 parts of nano-silicon dioxide, 10 parts of shell powder and 5 parts of diatomaceous earth. The remaining components, component contents and preparation methods are the same as those in Example 1.
[0105] Example 6
[0106] This embodiment provides a polyamide samarium iron nitrogen magnetic composite material and a preparation method thereof, which is different from Example 1 in that dioctyl nylonate is not added to the lubricant, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0107] Comparative Example 1
[0108] This comparative example provides a polyamide samarium iron nitrogen magnetic composite material, which is different from Example 1 in that the samarium iron nitrogen powder is 88.4 parts, no deodorant, antioxidant and activated carbon powder are added, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0109] The preparation method of the polyamide samarium iron nitrogen magnetic composite material of this comparative example comprises:
[0110] (1) dissolving a phosphate coupling agent in an alcohol solution to obtain a phosphating solution (the amount of the alcohol solution added is based on the amount of the alcohol solution that can completely immerse the samarium iron nitrogen powder, and the amount of the phosphate coupling agent added is 1% of the mass of the phosphating solution), and immersing the samarium iron nitrogen powder in the phosphating solution for 24 hours;
[0111] (2) placing the samarium iron nitrogen powder soaked in step (1) into a drying oven and drying at 80° C. for 8 h to volatilize the alcohol and form an antioxidant layer on the surface of the samarium iron nitrogen powder;
[0112] (3) The samarium iron nitrogen powder, polyamide 12 resin and lubricant in step (2) are blended at a high speed at 100° C. for 30 minutes according to the proportion, and then extruded and granulated in a twin-screw extruder at a granulation temperature of 200° C. to obtain a polyamide samarium iron nitrogen magnetic composite material.
[0113] Comparative Example 2
[0114] This comparative example provides a polyamide samarium iron nitrogen magnetic composite material and a preparation method thereof, which is different from Example 1 in that: activated carbon powder is 0.3 parts, deodorant is 0.1 parts, antioxidant is 0.8 parts, lubricant is 0.3 parts, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0115] The present invention conducts odor emission test and fluidity test on the magnetic composite powders of Examples 1 to 6 and Comparative Examples 1 to 2, specifically using the following methods:
[0116] (1) VDA270-2018 was used to test the odor emission of the magnetic composite material. Specifically, the prepared magnetic composite material pellets were placed in a narrow-mouth reagent bottle and sealed for 96 hours. The bottle mouth was opened and 5 people evaluated the odor concentration respectively, with a score of 1 to 5. The average score was calculated. The lower the odor, the lower the score. The results are shown in Table 1.
[0117] (2) The material fluidity was measured using a melt indexer. The results are shown in Table 1.
[0118] Table 1
[0119]
[0120]
[0121] It is not difficult to see from Table 1 that the magnetic composite materials obtained in Examples 1 to 6 have a low odor level, a high melt index, and good fluidity. By adding a deodorant to the magnetic composite material, the pollutants generated by the magnetic powder and the binder during the extrusion granulation process can be adsorbed or absorbed, thereby eliminating the odor of the magnetic material.
[0122] It can be seen from Table 1 that, compared with Example 1, the odor levels of Examples 4 and 5 are slightly improved. This is mainly because when the content of calcium chloride and nano-silicon dioxide in the deodorant is too high or too low, it will affect the adsorption effect on the material.
[0123] By comparing Example 1 with Example 6, it can be seen that the fluidity of the magnetic composite material obtained in Example 6 is reduced. This is mainly because the lubricant used in Example 6 is only calcium stearate, while dioctyl nylonate is added to the lubricant used in Example 1, which can enhance the low-temperature performance of polyamide, improve the impact resistance and plasticization performance of the product, and further improve the fluidity of the material.
[0124] By comparing Example 1 with Comparative Example 1, it can be seen that when no deodorant, antioxidant and activated carbon powder are added to the magnetic composite material of Comparative Example 1, the odor level is significantly improved and the fluidity is also significantly reduced. The magnetic composite material of Example 1 can absorb the odor generated during the preparation process and eliminate the odor by adding deodorant and activated carbon, and the antioxidant is added to avoid oxidation of the material at high temperature, which is beneficial to improve the fluidity of the material.
[0125] Compared with Example 1, the odor level of Comparative Example 2 is increased. This is mainly because the amount of deodorant and activated carbon added to the magnetic composite material of Comparative Example 2 is too low, resulting in a decrease in the odor removal effect and failure to effectively eliminate the odor.
[0126] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A magnetic composite material, characterized in that: In parts by mass, the magnetic composite material comprises: Magnetic powder 75-90 parts by mass; 10 to 25 parts by weight of binder; Deodorant 0.3-0.8 parts by mass 2. The magnetic composite material according to claim 1, characterized in that: The magnetic powder includes at least one of samarium iron nitrogen, neodymium iron boron, ferrite, neodymium iron nitrogen and manganese bismuth; Preferably, the binder comprises at least one of polyamide, polyolefin and polyester.
3. The magnetic composite material according to claim 1 or 2, characterized in that: The deodorant comprises calcium chloride, nano silicon dioxide, shell powder and diatomaceous earth; Preferably, the content of calcium chloride is 35 to 45 parts by mass; Preferably, the content of the nano-silicon dioxide is 25 to 35 parts by mass; Preferably, the content of the shell powder is 10 to 20 parts by mass; Preferably, the content of the diatomaceous earth is 10 to 20 parts by mass.
4. The magnetic composite material according to any one of claims 1 to 3, characterized in that: The magnetic composite material also includes antioxidants, activated carbon and additives; Preferably, the content of the antioxidant is 0.1 to 0.2 parts by mass; Preferably, the antioxidant comprises a hindered phenol antioxidant; Preferably, the content of the activated carbon is 0.5 to 1 parts by mass.
5. The magnetic composite material according to any one of claims 1 to 4, characterized in that: The surface of the magnetic powder is coated with an anti-oxidation layer; Preferably, the anti-oxidation layer comprises a phosphating agent; Preferably, the content of the phosphating agent is 0.5 to 1 parts by mass; Preferably, the phosphating agent comprises a phosphate coupling agent.
6. The magnetic composite material according to claim 4 or 5, characterized in that: The auxiliary agent also includes one or a combination of at least two of a lubricant, a stabilizer and a plasticizer; Preferably, the lubricant comprises a metal stearate and dioctyl nylonate; Preferably, the mass ratio of the metal stearate to dioctyl nylonate is (2-4.5):
6.
7. A method for preparing the magnetic composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises: The magnetic powder is surface treated so that an anti-oxidation layer is formed on the outer surface of the magnetic powder, and then a binder is added and mixed with a deodorant, and extrusion granulation is performed to obtain the magnetic composite material.
8. The preparation method according to claim 7, characterized in that: The surface treatment includes: Dissolving a phosphating agent in an organic solvent to obtain a phosphating solution, immersing the magnetic powder in the phosphating solution, and performing a heating treatment to evaporate the organic solvent to form the anti-oxidation layer on the outer surface of the magnetic powder; Preferably, the mass of the phosphating solution is recorded as 100%, and the amount of the phosphating agent added is 0.5-1%; Preferably, the organic solvent comprises anhydrous ethanol or acetone; Preferably, the soaking time is 18 to 30 hours; Preferably, the temperature of the heating treatment is 70-90°C; Preferably, the heating treatment time is 6 to 8 hours.
9. The preparation method according to claim 7 or 8, characterized in that: The mixing comprises: blending the magnetic powder coated with the anti-oxidation layer, the binder and the deodorant at a temperature of 80 to 120°C; Preferably, the mixing time is 25 to 45 minutes.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The extrusion granulation temperature is 190-220°C; Preferably, the extrusion granulation adopts a twin-screw extruder.
Citation Information
Patent Citations
High-performance polyamide / samarium-iron-nitrogen magnetic composite material and preparation method thereof
CN106349686A
Preparation method of samarium-iron-nitrogen / nano-iron composite bonded permanent magnet
CN111403165A
Samarium-iron-nitrogen magnet and preparation method thereof
CN114220648A